Kemampuan Literasi Membaca Siswa Kelas III SDN 19 Pinggir Kecamatan Pinggir Kabupaten Bengkalis Riau - Mursida Mursida; Wan Azura; Irasari Irasari; Ummi Muklisa (EL-EMIR Institute, 2025)
This study aims to analyze children’s reading literacy skills among third-grade students at SDN 19 Pinggir. Reading literacy is a very important foundation in children’s cognitive and academic development, as it serves as the basis for understanding various school subjects. Reading literacy not only includes the ability to recognize letters and words, but also involves comprehension of reading texts, critical thinking skills, and the ability to retell information that has been read, both orally and in written form. This research employed a qualitative approach, with data collection techniques consisting of observation and interviews. The research sample comprised one group of third-grade students at SDN 19 Pinggir, totaling two students. Data analysis was conducted by examining the results of interviews and field notes collected by the researcher during the research process. The findings indicate that students who receive support from a home environment rich in literacy activities, along with guidance from teachers who implement active learning approaches, tend to demonstrate better reading abilities. Therefore, it can be concluded that parental involvement, effective teaching strategies, and the availability of age-appropriate reading materials are important factors in improving reading literacy skills among elementary school students.